Yam addition in passion fruit juice: optimization of the consumer acceptance - Rodrigues, Jéssica Ferreira; Bastos, Sabrina Carvalho; Nunes, Cleiton Antônio; Pinheiro, Ana Carla Marques (MAGISTRA, 2017)
Abstract: Besides the interest in raw materials that can be used to enrich industrialized food with fiber, developing products based on tropical roots of traditional farming and crop as yam, has gained the interest of farmers and industries as it would enable the increment in the entire production chain. This study aimed to determine the best formulation of passion fruit juice added to yam through sensory tests. For this, the Central Composite Rotational Design was used as a tool to determine the best juice formulation. Results were analysed by using external preference mapping and through response surface, studying three variables (concentrations of yam, passion fruit juice concentrate and sugar) in five levels. As dependent variable the sensory characteristics of the juice (taste, texture, color, appearance, overall impression and purchase intent) were determined. Acceptance tests were conducted in laboratory with 50 consumers and the data were analysed using software Statistica version 5.0. It was observed that to achieve good acceptability (up "6-like slightly"), the product should be prepared using concentrations of yam, sugar and passion fruit juice concentrate around 10%, 6% and 18% respectively. Since the higher the concentration of yam, the greater must be the concentration of sugar and juice to obtain a better product acceptance (up "6-like slightly"). Key words: Central composite rotational design, Principal component analysis, Acceptance test.